PERFORMANCE MEDIATION ON THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL COMMITMENT ON TEACHER CAREER DEVELOPMENT STATE JUNIOR HIGH SCHOOL OF SERDANG REGENCY, BEDAGAI - Irham Lubis; Ivana Supi Al’amudi; Sarwoto; Willy Cahyadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
abstract